Development of Chemistry Magazine Containing Content on Cross-Aldol Condensation Reaction as Reading Material for Polyfunctional Organic Compounds Lectures - Rahmawati, Rahmawati; Hidayah, Weny Amanatul; Al Idrus, Syarifa Wahidah (Jurnal Pijar Mipa, 2025)
Chemistry magazines have the potential to be effective media because they are able to present material in a more interesting, concise manner, and are supported by visualizations that clarify abstract concepts. The use of chemistry magazines is expected to help students deepen their understanding of the aldol condensation reaction mechanism and other organic materials. This study aims to develop a chemistry magazine that contains content on the cross-aldol condensation reaction mechanism as a supplementary reading for students in the Polyfunctional Organic Compounds course. The type of research used is research and development (R&D) with a 4D model that includes the stages of define, design, develop, and disseminate. The subjects of the study were students from the Chemistry Education Study Program at the University of Mataram, while the object of the research was a chemistry magazine developed based on the results of a student needs analysis. Data were collected through expert validation sheets and student response questionnaires, then analyzed descriptively and quantitatively using Aiken's V formula to measure validity and percentage of agreement (PA) to measure reliability. The results showed that the chemistry magazine obtained an average validity score of 0.93, categorized as “highly valid,” and a reliability level of 94%, categorized as “reliable.” Meanwhile, the results of the practicality test, as obtained by students, achieved a percentage of 85% with the category “very practical”. Thus, the chemistry magazine developed is declared feasible and practical for use as additional reading material to enhance students' understanding of the cross-aldol condensation reaction mechanism in the Polyfunctional Organic Compounds course and to foster an interest in learning chemistry independently.